1997
DOI: 10.1159/000189495
|View full text |Cite
|
Sign up to set email alerts
|

<i>Helicobacter</i><i>pylori</i> in Kidney Allograft Recipients: High Prevalence of Colonization and Low Incidence of Active Inflammatory Lesions

Abstract: Since kidney transplant recipients are at enhanced risk for developing severe upper gastrointestinal disease and Helicobacter pylori (Hp) is an important pathogen in active gastritis and peptic ulcer, we performed gastroduodenoscopic examination, coupled with assessment of Hp colonization in 29 renal allograft recipients complaining of recurrent dyspepsia. Results were compared with those of 25 chronically hemodialyzed patients and 16 subjects free from renal disease, also suffering from upper gastrointestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 10 publications
1
22
2
Order By: Relevance
“…Depending on different studies and methods, the prevalence ranges from 34 to 75% [3, 4, 5, 6, 7]. The 13 C Urea Breath Test ( 13 C UBT) is a new diagnostic approach with a sensitivity of 90–100% and a specificity that ranges from 78 to 100% [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on different studies and methods, the prevalence ranges from 34 to 75% [3, 4, 5, 6, 7]. The 13 C Urea Breath Test ( 13 C UBT) is a new diagnostic approach with a sensitivity of 90–100% and a specificity that ranges from 78 to 100% [8].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, different cutoff points must be adopted according to several demographic and clinical variables in order to provide different levels of specificity and sensitivity. Although there are several reports on Hp prevalence in uremic patients determined by serology [3, 7, 11], there is scarce information regarding its utility for diagnosis of Hp infection in these patients [3]. Moreover, its usefulness for monitoring eradication therapy on hemodialysis (HD) patients is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…When the prevalence in transplant recipients is compared with that in the control groups, four [4,6,9,12] of six studies showed no significant difference between renal transplant recipients and nonrenal disease individuals. In contrast, one study [8] showed a lower prevalence and one [10] showed a higher prevalence in renal transplant recipients than in nonrenal disease individuals and hemodialysis patients, but on the whole the prevalence of H. pylori infection in organ transplant recipients appears to be similar to that in control individuals. Interestingly, some studies showed that the prevalence of H. pylori infection decreased after transplantation.…”
Section: Introductionmentioning
confidence: 69%
“…To clarify the relationship between H. pylori infection and peptic ulcer disease after solid-organ transplantation, the reported prevalence of gastric ulcers and duodenal ulcers and H. pylori status are also summarized in Table 1 and Table 2. The prevalence of peptic ulcer in renal transplant recipients was similar [4,6,10] or slightly lower [9] than in nonrenal disease patients, hemodialysis patients, or both. In renal transplant recipients, H. pylori-positive patients had a higher prevalence of peptic ulcer than H. pylori-negative recipients in three studies [3 ,7,11], whereas one study [5] showed no significant difference between H. pylori-positive and H. pylori-negative patients.…”
Section: Relationship Of Helicobacter Pylori Infection To Peptic Ulcementioning
confidence: 78%
“…How the Th2 profile may be important in balancing the immune response is demonstrated by other clinical and experimental observations. For example, in pregnancy, the immune system of the mother undergoes a complex modification characterized by a preferential Th2 “switch“ that enables the mother to “tolerate“ her offspring by inhibiting Th1 response, which would otherwise promote fetus rejection 4–6. Whatever the immune mechanism elicited may be, these cases show that the role of H. pylori infection as a trigger or protective factor for the onset of CD should be still clarified.…”
mentioning
confidence: 99%